Urinary Metabolomics Study of the Intervention Effect of Hypoglycemic Decoction on Type 2 Diabetes Mellitus Rats Model. (30th October 2019) - Pan, Lin-Lin; Sun, Qi-Hui; Liu, Gui-Rong; Guo, Jia-Yin
Abstract : The hypoglycemic decoction (HD) is a traditional Chinese medicine (TCM) preparation for the treatment of diabetes mellitus (DM), with a remarkable therapeutic effect. However, its mechanism of action is still unclear at the metabolic level. In this study, the biochemical markers from type 2 DM (T2DM) rats, induced by a high-sugar and high-fat diet combined with streptozotocin (STZ), were detected. The metabolomics-based analysis using high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS) was conducted to evaluate urine samples from control, model, metformin, and HD groups. After oral administration of HD for 28 days, the general state, weight, fasting blood glucose (FBG), blood lipid level, oral glucose tolerance test (OGTT), fasting insulin (FINS), insulin sensitivity index (ISI), and homeostasis model assessment of insulin resistance (HOMA-IR) were significantly improved (P < 0.01 ). The western blotting showed that HD can enhance the protein expression of glucose transporter 4 (GLUT4) and adenosine monophosphate-activated protein kinase (AMPK). The metabolomics results revealed that after treatment with HD, the levels of L-carnitine, 1-methyladenosine, 1-methylhistamine, and 3-indoleacrylic acid were upregulated and the levels of riboflavin, phenylalanine, atrolactic acid, 2-oxoglutarate, citrate, isocitrate, cortisol, and glucose were downregulated. The main mechanism may be closely related to the regulation of the tricarboxylic acid (TCA) cycle, phenylalanine metabolism, glyoxylate metabolism, and dicarboxylate metabolism. Additionally, it was also found that HD can regulate the protein expression of GLUT4 and AMPK to interfere with TCA cycle and carbohydrate metabolism to treat T2DM.